A retrospective case-cohort study comparing treatment outcomes in abacavir versus stavudine containing first line antiretroviral treatment regimens in children <3yrs old, at a paediatric programme based in Soweto, South Africa. - Haseena Cassim (PLoS ONE, 2017)
The current World Health Organization guideline for first line antiretroviral therapy (ART) in HIV-infected children recommends the use of abacavir and lamivudine as nucleoside backbones and no longer includes stavudine. We compared treatment outcomes with abacavir (ABC) versus stavudine (d4T) in a cohort of HIV-1 infected children 6 and 12 months after antiretroviral therapy was initiated.This was a retrospective case-cohort study, using programmatic data from children enrolled in the Paediatric Wellness Programme at the Perinatal HIV Research Unit in Soweto, South Africa between 2005 and 2013. Children on abacavir/stavudine who had initiated ART at age <3 years with a regimen including lamivudine and lopinavir/ritonavir and had at least one 6 or 12 month viral load result were eligible. All ABC cases identified were matched for age at ART initiation and gender to eligible d4T controls (1:2). Outcomes analysed at 6 and 12 months post ART initiation included virological failure, mortality, immunological failure and anthropometry. Chi-square tests compared categorical measures while Kruskal-Wallis compared continuous measures.We identified 57 eligible ABC cases and selected 114 matched d4T controls. Overall, 57% were females and 89% started treatment at age <1year. The median age at ART initiation was 3.11 (IQR: 1.98-6.05) months. There was no difference in the proportion of children virologically suppressed between the groups at 6 (ABC 54.5% vs. d4T 67.0%, p = 0.125) and 12 (ABC 66.7% vs. d4T 71.6%, p = 0.53) months post ART-initiation. The proportion of children with adherence levels >90% for ABC and d4T were similar too (95% in ABC vs. 86% in d4T, p = 0.10). The proportion of children who died over 12 months was 3.5% in the ABC and 7.9% in the d4T group (p = 0.27). Similarly, the anthropometric measures were comparable.It is reassuring that in the short term, in this group of patients, the treatment outcomes were similar.